Enhancing intra-SAARC trade: Pruning India's sensitive list under SAFTA - Nisha Taneja; Saon Ray; Neetika Kaushal; Devjit Roy Chowdhury (Indian Council for Research on International Economic Relations (ICRIER), 2011)
The study suggests an approach to reduce India's sensitive list under SAFTA. The concept of Revealed Comparative Advantage has been used to pair the RCAs for products on India's sensitive list with the corresponding RCAs of the SAARC countries. Four categories of items are generated based on whether India or the SAARC country is competitive in each of the items. This process helps in identifying items in which India is competitive and those where the exporting SAARC country is not competitive. Such items are recommended for removal from India's sensitive list. Items that are vulnerable to competition include those items where the exporting country is competitive but India is not. Such items can remain on the sensitive list and can be removed gradually in a phased manner.
Keywords: F14; O25; 330; Sensitive List; Regional Agreements; SAFT; Komparativer Vorteil; Indien; Freihandelszone; Handelsabkommen; Südasien